Incorporação da pectina do maracujá-amarelo (Passiflora edulis Flavicarpa) em filmes biodegradáveis a base de proteínas do subproduto de peixes - Florentino, Gabrielle Ingrid Bizerra (2022)
The development of bioplastics based on renewable raw materials has emerged as an innovative option in the food industry scenario. The application of fish proteins in the production of bioplastics gives rise to films with good barrier properties, but with unsatisfactory mechanical characteristics such as high rigidity and low malleability. The incorporation of pectin into protein bioplastics can improve the physical and mechanical properties of the film compared to protein-based bioplastics or pectin alone. In this context, the objective was to maximize the conditions for the production of biodegradable bioplastic from proteins from the by-product of the spearfish (Scomberomorus brasiliensis) and pectin from the yellow passion fruit (Passiflora edulis Flavicarpa). In the first stage of the experiment, the myofibrillar proteins extracted from the by-product of the sawfish were evaluated and the degree of esterification and acetylation of the pectin obtained from the passion fruit peel was determined. Then, the myofibrillar protein and extracted pectin were used to determine the optimal conditions for obtaining the biodegradable bioplastic, using response surface methodology. The myofibrillar protein extracted from the sawfish presented 72.42% of proteins, mainly myofibrillar, and 2,38% of lipids, while the pectin extracted from the passion fruit had a high content of methoxylation (88,95%) and low content of acetylation (5,37%). The bioplastic made with 5% protein concentrate and 3% yellow passion fruit pectin showed the lowest values of water vapor permeability (PVA) and higher tensile strength (RT). The maximized bioplastic showed satisfactory characteristics such as good tensile strength (4.91 MPa), low water vapor permeability (0.9x10-2 gH2O.mm/m2 .h.mmHg), flexible (264,87%) , yellowish color, good thermal stability, low solubility (18,82%), biodegradable, semi-crystalline and amorphous, favorable compatibility between myofibrillar and pectin protein chains, smooth and homogeneous surface, indicating that the extracted biopolymers can be used to produce bioplastics biodegradable.